"It´s like walking in a bubble", nursing students´ perspectives on age suit simulation in a home environment - group interviews from reflection seminars - Björn Bouwmeester Stjernetun; Catharina Gillsjö; Elzana Odzakovic; Jenny Hallgren (BMC, 2024)
Abstract Background Older persons with age-related and complex health problems will increasingly depend on care provision from nurses in their own homes. However, a barrier to quality care is ageism and nursing students´ disinterest in geriatrics. In addition, nurse education often falls short in preparing students for the complexity of geriatric care. Welfare technology (WT) is progressively implemented in home care to help older persons live at home despite their health problems. However, this process is intricate and requires acceptance and digital literacy among caregivers and older persons. Despite these challenges, nurse education can address and change negative attitudes through innovative teaching methods such as age suit simulation. Therefore, the study aims to describe nursing students´ experiences of age suit simulation in a home-like environment with WT and technical aids, and will reveal their perspective on ageing and providing care to older adults. Methods A qualitative explorative design using semi-structured group interviews (n=39) among nursing students. Data was analysed through reflexive thematic analysis. Results The analysis generated three main themes; "It's like walking in a bubble", "An eye opener" and "Concerns about ageing and the current structure of geriatric care". The main themes included eight subthemes. Adapting to the sensory and physical limitations of the age suit was an immersive experience and caused feelings of frustration, loneliness and disconnection. A prominent result was a raised awareness of cognitive loss, especially impaired vision, and students felt the simulations had made them aware of the everyday challenges older persons faced. Students highlighted the importance of patience and giving enough time in care situations by being present and having a critical perspective of WT. The students were mostly negative towards their own ageing and could better relate to older persons´ vulnerability. Conclusions Age suit simulation was described as an embodied and eye-opening experience, raising nursing students´ awareness of older persons´ functional limitations and the consequences for dignity and independence. Coping with cognitive loss was especially difficult. Students were motivated to apply their new knowledge to clinical practice. Age suit simulation can complement geriatric education, preparing students for the complex care needs of older persons.